Caracterização da macrofauna bentônica de bancos areno-lamosos dos estuários dos rios Pacoti e Pirangi - Silva, Aline Ferreira da (2011)
The distribution of organisms regarding their habitat plays an important role in ecological studies. The nature of this distribution provides an initial view on the types of ecological processes regulating the assemblages and the populations. The present study aims to characterize and to compare the benthic macroinfauna community structure, correlating it with the environmental conditions at the muddysand flats at the Pacoti and the Pirangi estuaries. In February 2005, 45 samples were collected in each estuary, sample were preserved in formol, passed through a 0,3mm mesh, dyed with rose, sorted and the organisms identified. The amount of shingle, sand, silt, and clay presented significant differences (p<0,05) between the two estuaries. At Pacoti estuary, Laeonereis culveri presented the highest density (10,423 ind/m2) and, at Pirangi estuary, Tagelus plebeius was the dominant species with a density of 910.35 ind/m2. Analysis pointed out a strong negative correlation between the average abundance and the organic matter, and between the average abundance and clay at the Pirangi estuary. At the Pacoti estuary, a strong positive correlation was observed out between the richness and several parameters such as the mean grain size, organic matter, and silt. A negative correlation between the richness and the amount of sand was also evidenced at the same estuary. The average abundance was higher at Pacoti, whereas richness, equitability, and diversity were higher at Pirangi. At the Pacoti estuary, the cluster analysis revealed a highly homogeneous muddy-sand flat, with strong similarity among samples. On the other hand, Pirangi was more heterogeneous with a lower similarity degree. The BIOENV analysis discriminated grain selection, CaCO3, and the amount of organic matter as the abiotic factors that best explain the structure of benthic macroinfauna communit’s in the muddy-sand flat at Pacoti. At the Pirangi estuary, the relevant abiotic factors were the shingle and fine sediment percentage.